Odpowiedzi

2010-03-21T20:44:33+01:00
B) 2x-2=7-x
2x-2-7+x=0
x-9=o/+9
x=9

a)-3x=2x-10
-3x-2x-10=0
-5x-10=0
-5x=10
x= 2
Najlepsza Odpowiedź!
2010-03-21T20:50:46+01:00
A)-3=2x-10
-3x-2x=-10
-5x=-10 | : (-5)
x=2

b) 2x-2=7-x
2x+x=7+2
3x=9 |:3
x=3

c) 10=4-2x
2x=4-10
2x=-6 |:2
x=-3

d) -(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3 |:-(2)
x=-1,5

e) 2(x+1)=x
2x+2=x
2x-x=-2
x=-2

f) 2t-(3t+1)=6
2t-3t-1=6
2t-3t=6+1
-1t=7 |:(-1)
t=-7

g) -(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0

i) (x-7)-2(3x+5)=3
x-7-6x-5=3
x-6x=3+7+5
-5x=15 |:(-5)
x=-3


Sądzę, że wszystko jest dobrze :) i liczę na NAJ :)